The Concept of Enculturation in a Multidisciplinary Approach: Philosophical, Educational, Cultural Anthropological and Ethnographic Aspects - Vehrer, Adél (Acta Cultura et Paedagogicae, 2024)
The forms of early education for children have remained essentially unchanged for centuries. In examining this, the observations of ancient philosophers coincide with the findings of 20th century social science research. The present paper reviews the terminology, definitions and interpretations of this early phase of education. The main key concepts discussed are inculcation (cultural integration), enculturation and socialization.